Perfil de competências na formação de enfermeiros : validação por docentes e acadêmicos de enfermagem - Ormonde Júnior, Juarez Coimbra (2017)
ABSTRACT: The purpose of this study was to validate the content of a competency profile for the training of generalist nurses. The starting point of the research was a profile of competencies, elaborated by professors of the Nursing Faculty of the Federal University of Mato Grosso, Cuiabá campus, who considered the areas of health care, administration and management, education and knowledge production. We take as central reference of analysis the conceptual understanding of competences in nursing training. It is a research of mixed methods, using the Delphi technique. Participants were specialists in nursing education in Brazil, teachers and academics from two higher education institutions in Mato Grosso. For the quantitative-qualitative analysis of the answers, the researchers adopted the methodological reference of the research of mixed methods. The analysis of the quantitative answers of the questionnaire was carried out using simple descriptive statistics, by means of the calculation of the confidence interval and p value. In order to evaluate the agreement, we used a calculation of the Content Validity Index, previously established in ≥70% for the mean of the sum of the Likert scale responses, corresponding to the "totally agree" and "partially agree" items. The qualitative analysis was performed to support the modifications in the profile and to analyze the participants 'understanding of the nurses' areas of action. The study complied with all formal requirements contained in national and international standards regulating research involving human subjects. The profile was validated with 26 specialists in nursing education, for the four competencies proposed: Health Care (96.20%), Administration and Management (92.30%), Education (88.50%) and Knowledge Production (96.20%). Based on the suggestions and recommendations of the specialists, changes were made, generating a new version of the competency profile that was submitted to the validation, concurrently, with nursing and academic professors who were attending the 8th semester and 9th semester of two undergraduate courses in Institutions. Competences were validated with the following results: Health Care (98,80%), Health and Nursing Management (98,80%), Education (97,60%) and Knowledge Production (97,60%). Based on the contributions of teachers and academics, the last version of the profile was generated. The qualitative analysis of the suggestions at the end of the study sought to understand which elements the participants judged necessary for the training of generalist nurses. The validation carried out with specialists, academics and teachers shows that the profile includes the essential skills to be developed in the process of training nurses. The profile generated can be used by the nursing faculties as a guide of possible restructuring in the pedagogical projects of the courses.